Pemaknaan Homonimi Dalam Dialog Film Laskar Pelangi Sebagai Media Pembelajaran Kosakata Bahasa Indonesia - Melly Destryani Utami; Nurulanningsih Nurulanningsih (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to analyze the forms and meanings of homonyms in the dialogues of the film *Laskar Pelangi* by Riri Riza and to assess their suitability as teaching materials for Indonesian vocabulary. This study employs a qualitative descriptive approach using content analysis on 123 dialogues, which were designated as units of analysis. The research data consists of words that meet the criteria for homonymy based on similarity in form, difference in meaning, and contextual relevance. The results indicate the presence of 20 instances of homonymy, evenly divided into 10 cases of pure homonymy and 10 cases of partial homonymy. Analytically, the findings reveal that homonymy in films tends to occur in lexemes closely related to the characters’ daily experiences and shifts from concrete to more abstract meanings, such as “road,” “heat,” “head,” and “hard.” Their meanings cannot be explained by lexical factors alone but are determined by multimodal context, namely the scene’s situation, inter-character relationships, intonation, and expressions. The suitability of films as teaching materials is demonstrated by three factors: the use of lexemes familiar to students, the presence of a clear social context, and the availability of audiovisual cues that aid in meaning interpretation. Thus, this study contributes to semantic research by emphasizing the importance of multimodal context in the interpretation of homonyms, while also proposing films as a medium for contextual and interpretive vocabulary learning.